Designing and Dressing Method of Worm Grinding Wheel for Grinding Process of Face Gear - Wang Xiaojun; Li Xiaozhen; Ye Wen (Jixie chuandong)
In order to process the hardened face gear,and improve the application of face gear in aeronautics industry,the grinding process of face gear is studied. A worm grinding wheel for grinding process of the face gear is studied in design and dressing method. According to the meshing relationship of face gear,worm grinding wheel and medium gear,the coordinate systems of face gear,worm grinding wheel and medium gear are set up. Combing the relationship between the tooth profile equation and the coordinate transformation and using the enveloping theory,the tooth profile equation of face gear,worm grinding wheel and medium gear are deduced,the processing method of worm grinding wheel and face gear is obtained. Through the numerical computation method,the tooth profile simulation of face gear and grinding wheel is carried out,the 3D model of face gear,worm grinding wheel and medium gear are set up. The approach and principle of dressing are studied,the simulation of dressing process is carried out,and a basis of grinding process of face gear is provided.